Coronary microvascular dysfunction is associated with impaired cognitive function: the Cerebral-Coronary Connection study (C3 study). (7th November 2022) - Mejia-Renteria, Hernan; Travieso, Alejandro; Matías-Guiu, Jordi A; Yus, Miguel; Espejo-Paeres, Carolina; Finocchiaro, Francesca; Fernández, Sara; Gomez-Escalonilla, Carlos Ignacio; Reneses-Prieto, Blanca; Gómez-Garré, Maria Dulcenombre; Delgado-Alvarez, Alfonso; Bustos, Ana; et al.
Abstract: Background: It remains unknown whether the presence of coronary microcirculatory dysfunction (CMD) correlates with its equivalent condition in the brain, cerebral small vessel disease (CSVD). The cerebral-coronary connection (C3), a prospective blinded study, investigated the prevalence of CMD in patients with coronary artery disease (CAD) and its association with CSVD and cognitive function. Methods and results: Patients with documented CAD fulfilling inclusion criteria underwent physiological assessment of epicardial vessels and the microcirculation using intracoronary pressure and Doppler. Coronary microcirculation-related indices included coronary flow reserve (CFR) and hyperaemic microvascular resistance. Brain magnetic resonance imaging, transcranial Doppler (TCD), and neurocognitive examination were performed. Overall, 67 patients were included in the study (mean age 66 years, 73% female). Patients with abnormal CFR (<2.0) (55.2%) showed higher burden of white-matter hyperintensities: 43.2 vs. 20.0% ( P = 0.044). After statistical adjustment, low CFR was associated with lower grey matter volume ( P = 0.024) and with parameters of white-matter microstructural damage in diffusion-tensor imaging (lower fractional anisotropy and higher mean diffusivity, P = 0.029 and P = 0.032, respectively). Low CFR was associated with higher resistive ( P = 0.027) and pulsatility ( P = 0.043) values on TCD, and worse neurocognitive test scores (lower mini mental state examination, P = 0.025, and slower Trail Making Test A, P = 0.034). Conclusions: Coronary microcirculatory dysfunction is frequent in patients with CAD and correlates with CSVD, abnormal cerebral flow haemodynamics, and significant cognitive impairment. These findings support the hypothesis that microvascular dysfunction in the heart and the brain are part of a single pathological process affecting microcirculation in patients with CAD. Clinical Trial Registration: ClinicalTrials.gov NCT04131075. Structured Graphical Abstract: Structured Graphical Abstract CFR, coronary flow reserve; FFR, fractional flow reserve; MMSE, mini mental state examination; ACE-III, Addenbrooke's Cognitive Examination (attention domain); TMT-A, Trail Making Test A; MRI, magnetic resonance imaging; WMH, white-matter hyperintensity; FA, fractional anisotropy; MD, mean diffusivity; GM, grey matter.